Charting the future of marine biotechnology: educational strategies for empowering Europe’s blue bioeconomy workforce - Marija Kataržytė; Anna Toruńska-Sitarz; Donata Overlingė; Lada Lukić Bilela; Susana P. Gaudêncio; Nerijus Nika; Ana Rotter; Xenia Theodotou Schneider; Jeronimo Chirivella; Inga Matijošytė; Laura Grundmane; Belma Kalamujić Stroil; et al. (Frontiers in Marine Science, 2026)
This study provides useful insight into the current state and recent developments in blue (marine) biotechnology education (BBE) in Europe. A questionnaire assessing awareness and interest in blue biotechnology (BB) was conducted among students in their final year of upper secondary school in a selection of European countries. Results demonstrate that there are great regional differences in students’ recognition of BB; recognition of BB is relatively poor (though biotechnology knowledge is relatively good). This illustrates the lack of early education and ocean literacy. The interest in BB studies varied by country. Non-formal science, technology, engineering, and mathematics (STEM) activities, especially visits to research institutes and private businesses, help raise awareness. The review of education programs conducted in this study revealed that only a small number of programs are dedicated to BB and that it is not well integrated into existing curricula. Early ocean literacy, lifelong learning opportunities, and the inclusion of entrepreneurship and interdisciplinary skills in education are essential for developing a workforce capable of driving the future of the blue bioeconomy within the broader objectives of the EU Blue Economy Strategy and European Union (EU) Bioeconomy Strategy. To advance BBE, we propose the following recommendations: 1) incorporate and increase ocean literacy and BBE at the primary and secondary school levels; 2) support lifelong learning and adaptation to emerging technologies; 3) build collaborative ocean education networks; 4) bridge education communities, research and industry; 5) encourage entrepreneurship; 6) harmonise postgraduate BB programs; 7) establish joint European MSc and PhD degrees; and 8) align funding and BBE activities with national and regional gross domestic product (GDP) contributions for the BB sector.

Comparative assessment of pelagic/benthic microalgae in the oligotrophic continental shelf of Heraklion Bay, Eastern Mediterranean: A pigments-based chemotaxonomic analysis - Ben Möller; Eleni Livanou; Stella Psarra; Panayota Koulouri; Costas Dounas; Ana Rotter; Manolis Mandalakis (Regional Studies in Marine Science, 2025)

Exploring marine microbial diversity: an overview of representative sampling strategies - Zrinka Ljubešić; Marija Gligora Udovič; Donata Overlingė; Filip Grgurević; Füsun Akgül; Ariola Bacu; Ana R. Díaz-Marrero; Dragana Drakulović; Stefano Fazi; Susana P. Gaudêncio; Anamarija Kolda; Lucie Novoveska; et al. (Frontiers in Marine Science, 2025)
The assessment of marine microbial biodiversity is crucial for determining either the environmental status (ecological or biodiversity research) or as a first step in the biodiscovery process (biotechnological research). Regardless of the research purpose, the first step in a biodiversity assessment is sampling, which can range from ad hoc sampling expeditions to long-term monitoring campaigns. In spite of its demands for funds, infrastructure, expertise, equipment, and personnel, sampling is often not adequately planned. This results in increased likelihood for biased sampling, which can lead to misinterpretation of results, omission of valuable specimens and an unrepresentative collection of stored samples, all particularly important for the assessment of microbial biodiversity. For these reasons, we are proposing a conceptual framework to assist in better preparation of sampling, consisting of pre-sampling, sampling and post sampling steps. The manuscript guides the reader through all the necessary steps, regardless of the sampling habitat (from water column to sediment), the sampling techniques and the preservation and storage approaches including culture and biorepositories. Such a harmonized approach can be of benefit for (i) researchers in the field of ecology/biotechnology, (ii) industrial companies requiring information on the providers and availability of data, and (iii) governance structures and funders, in the light of open science principles.

From the sea to aquafeed: A perspective overview - Orhan Tufan Eroldoğan; Brett Glencross; Lucie Novoveska; Susana P. Gaudêncio; Buki Rinkevich; Giovanna Cristina Varese; Maria de Fátima Carvalho; Deniz Tasdemir; Ivo Safarik; Søren Laurentius Nielsen; Céline Rebours; Lukić Bilela Lada; et al. (Reviews in Aquaculture, 2023)
Aquaculture has been one of the fastest‐growing food production systems sectors for over three decades. With its growth, the demand for alternative, cheaper and high‐quality feed ingredients is also increasing. Innovation investments on providing new functional feed alternatives have yielded several viable alternative raw materials. Considering all the current feed ingredients, their circular adaption in the aquafeed manufacturing industry is clearly of the utmost importance to achieve sustainable aquaculture in the near future. The use of terrestrial plant materials and animal by‐products predominantly used in aquafeed ingredients puts a heavily reliance on terrestrial agroecosystems, which also has its own sustainability concerns. Therefore, the aquafeed industry needs to progress with functional and sustainable alternative raw materials for feed that must be more resilient and consistent, considering a circular perspective. In this review, we assess the current trends in using various marine organisms, ranging from microorganisms (including fungi, thraustochytrids, microalgae and bacteria) to macroalgae and macroinvertebrates as viable biological feed resources. This review focuses on the trend of circular use of resources and the development of new value chains. In this, we present a perspective of promoting novel circular economy value chains that promote the re‐use of biological resources as valuable feed ingredients. Thus, we highlight some potentially important marine‐derived resources that deserve further investigations for improving or addressing circular aquaculture.

Editorial: Marine Biotechnology, Revealing an Ocean of Opportunities - Ana Rotter; Susana P. Gaudêncio; Arita Dubnika; Marlen I. Vasquez (Frontiers in Marine Science, 2022)

Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Vita Rudovica; Ana Rotter; Susana P. Gaudêncio; Lucie Novoveská; Füsun Akgül; Linn Kristin Akslen-Hoel; Diogo A. M. Alexandrino; Olga Anne; Lauris Arbidans; Miroslava Atanassova; Magdalena Bełdowska; Jacek Bełdowski; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland, and the Baltic Sea.

Grass Growth and N2O Emissions From Soil After Application of Jellyfish in Coastal Areas - Florian Borchert; Iraj Emadodin; Christof Kluß; Ana Rotter; Thorsten Reinsch (Frontiers in Marine Science, 2021)
The supply of nutrients for agricultural production faces enormous challenges as food security and sustainability goals have to be ensured. Processing of marine biomass has high potential to provide nutrients for agricultural purposes in coastal areas. One underexplored resource are jellyfish, which occur as blooms and by-catch of the fishing industry. In this context, a pot experiment investigated the effects of jellyfish as a fertilizer on biomass accumulation of annual ryegrass ( Lolium multiflorum ), and its effect on the important greenhouse gas N 2 O as a sustainability indicator of novel fertilizers. Dried and ground jellyfish was applied [3 species: Aurelia aurita (AA), Cyanea capillata (CC), Periphylla periphylla (PP)] and compared with an unfertilized and a mineral fertilized (calcium-ammonium-nitrate, CAN) treatment. Dried jellyfish and CAN were applied at equal N rates of 5 g N per m 2 . The N 2 O-fluxes from soil were measured over 56 days after fertilizer application. Grass dry matter yields, when using CC and PP treatments, were not significantly different to the CAN treatment ( p > 0.05). After reducing its salinity, AA also showed no differences to CAN on plant growth and the lowest coefficient of variation for dry matter yield as an indicator for yield stability. Accumulated N 2 O-emissions were lowest in the control and were 3-times higher in AA and CC compared to CAN ( p < 0.05). If salinity levels are moderate, jellyfish application to soil can compete with artificial mineral fertilizers in terms of N-supply for above- and belowground yield response, regardless of jellyfish species used. However, elevated N 2 O-emissions are likely to affect its suitability for large-scale application. Nevertheless, if energy-efficient methods of drying and desalination of jellyfish can be developed, in coastal areas dried jellyfish is a valuable fertilizer in coastal areas, particularly in situations where nutrient supplies for agriculture are limited.

Sequestration of Polystyrene Microplastics by Jellyfish Mucus - Živa Lengar; Katja Klun; Iztok Dogsa; Ana Rotter; David Stopar (Frontiers in Marine Science, 2021)
The worldwide microplastics pollution is a serious environmental and health problem that is currently not effectively mitigated. In this work we tested jellyfish mucus as a new bioflocculent material capable of sequestration of polystyrene microplastics in aqueous environments. Mucus material was collected from different jellyfish species and was used to trap fluorescently tagged polystyrene microspheres. The efficiency of removal was tested using varying concentrations of microplastics and mucus. The interaction between the microplastics and mucus was determined by viscosity measurements and confocal laser scanning microscopy. Different mucus preparation methods were also tested: freshly prepared, mechanically sheared, freeze-thawed, freeze-dried, and hydrolyzed mucus. The results demonstrate that jellyfish mucus can efficiently sequester polystyrene microplastics particles from the suspension. The fraction of the removed microplastics was highest with freshly prepared mucus and decreased with freeze-thawing and freeze-drying. The mucus ability to sequester microplastics was completely lost in the hydrolyzed mucus. The results imply that the intact jellyfish mucus has the potential to be used as a biopolymer capable of removing microplastics material.

A New Tool for Faster Construction of Marine Biotechnology Collaborative Networks - Ana Rotter; Susana P. Gaudêncio; Katja Klun; Jan-Niklas Macher; Olivier P. Thomas; Irem Deniz; Christine Edwards; Ernesta Grigalionyte-Bembič; Zrinka Ljubešić; Johan Robbens; Giovanna Cristina Varese; Marlen I. Vasquez (Frontiers in Marine Science, 2021)
The increasing and rapid development in technologies, infrastructures, computational power, data availability and information flow has enabled rapid scientific advances. These entail transdisciplinary collaborations that maximize sharing of data and knowledge and, consequently, results, and possible technology transfer. However, in emerging scientific fields it is sometimes difficult to provide all necessary expertise within existing collaborative circles. This is especially true for marine biotechnology that directly addresses global societal challenges. This article describes the creation of a platform dedicated to facilitating the formation of short or mid-term collaborative networks in marine biotechnology. This online platform ( https://www.ocean4biotech.eu/map/ ) enables experts (researchers and members of the marine biotechnology community in general) to have the possibility to showcase their expertise with the aim of being integrated into new collaborations/consortia on the one hand, or to use it as a search tool to complement the expertise in planned/running collaborations, on the other. The platform was created within the Ocean4Biotech (European transdisciplinary networking platform for marine biotechnology) Action, funded under the framework of the European Cooperation in Science and Technology (COST). To build the platform, an inquiry was developed to identify experts in marine biotechnology and its adjunct fields, to define their expertise, to highlight their infrastructures and facilities and to pinpoint the main bottlenecks in this field. The inquiry was open to all experts in the broad field of marine biotechnology, including non-members of the consortium. The inquiry ( https://ee.kobotoolbox.org/single/UKVsBNtD ) remains open for insertion of additional expertise and the resulting interactive map can be used as a display and search tool for establishing new collaborations.

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

Marine Environmental Plastic Pollution: Mitigation by Microorganism Degradation and Recycling Valorization - Juliana Oliveira; Afonso Belchior; Verônica D. da Silva; Ana Rotter; Željko Petrovski; Pedro L. Almeida; Nídia D. Lourenço; Susana P. Gaudêncio (Frontiers in Marine Science, 2020)
Plastics are very useful materials and present numerous advantages in the daily life of individuals and society. However, plastics are accumulating in the environment and due to their low biodegradability rate, this problem will persist for centuries. Until recently, oceans were treated as places to dispose of litter, thus the persistent substances are causing serious pollution issues. Plastic and microplastic waste has a negative environmental, social, and economic impact, e.g., causing injury/death to marine organisms and entering the food chain, which leads to health problems. The development of solutions and methods to mitigate marine (micro)plastic pollution is in high demand. There is a knowledge gap in this field, reason why research on this thematic is increasing. Recent studies reported the biodegradation of some types of polymers using different bacteria, biofilm forming bacteria, bacterial consortia, and fungi. Biodegradation is influenced by several factors, from the type of microorganism to the type of polymers, their physicochemical properties, and the environment conditions (e.g., temperature, pH, UV radiation). Currently, green environmentally friendly alternatives to plastic made from renewable feedstocks are starting to enter the market. This review covers the period from 1964 to April 2020 and comprehensively gathers investigation on marine plastic and microplastic pollution, negative consequences of plastic use, and bioplastic production. It lists the most useful methods for plastic degradation and recycling valorization, including degradation mediated by microorganisms (biodegradation) and the methods used to detect and analyze the biodegradation.

A New Network for the Advancement of Marine Biotechnology in Europe and Beyond - Ana Rotter; Ariola Bacu; Michèle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Meltem Conk Dalay; Thanos Dailianis; Irem Deniz; et al. (Frontiers in Marine Science, 2020)

Non-indigenous Species in the Mediterranean Sea: Turning From Pest to Source by Developing the 8Rs Model, a New Paradigm in Pollution Mitigation - Ana Rotter; Katja Klun; Janja Francé; Patricija Mozetič; Martina Orlando-Bonaca (Frontiers in Marine Science, 2020)

A perspective on the potential of using marine organic fertilizers for the sustainable management of coastal ecosystem services - Iraj Emadodin; Thorsten Reinsch; Ana Rotter; Martina Orlando-Bonaca; Friedhelm Taube; Jamileh Javidpour (Environmental Sustainability, 2020)
Agricultural production is predicted to double during the next century. To ensure food security in response to global population growth is a challenge and will require strategies that mitigate associated environmental damage in ways consistent with United Nation’s Sustainable Development Goals. One possible approach is to utilize organic fertilizers from marine sources to improve soil structure by enhancing activities of soil organisms and restoring essential plant nutrients to the soil. Here we identify opportunities to develop organic fertilizers from two types of materials of marine origin: seagrass wrack and jellyfish biomass. Seagrass wrack often occurs as undesirable waste material on beaches. In many coastal areas around the world jellyfish bloom presents a nuisance because of negative impacts on marine ecosystem productivity. Several investigations have reported that organic fertilizers produced from seagrass and jellyfish could enhance coastal ecosystem services by reducing pollution, and by improving soil health and quality. Recent research indicates that seagrass litter improves soil water holding capacity and the nutritional value of crops; moreover, it can be used as multi-functional fertilizer, due to its content of valuable macro- and microelements. The application of jellyfish fertilizer increases soil contents of organic matter, nitrogen, phosphorus and potassium and enhances the growth and survival of seedlings significantly. In this overview we describe novel approaches regarding the utilization of seagrass and jellyfish as sources of fertilizer, and experimental studies on the influences of marine organic fertilizers on soil restoration, and implications for coastal management.

Statistical modeling of long-term grapevine response to ‘Candidatus Phytoplasma solani’ infection in the field - Ana Rotter; Petra Nikolić; Neža Turnšek; Polona Kogovšek; Andrej Blejec; Kristina Gruden; Marina Dermastia (European Journal of Plant Pathology, 2018)

Influence of selected anti-cancer drugs on the induction of DNA double-strand breaks and changes in gene expression in human hepatoma HepG2 cells - Matjaž Novak; Bojana Žegura; Špela Baebler; Alja Štern; Ana Rotter; Katja Stare; Metka Filipič (Environmental Science and Pollution Research, 2016)

Potato virus Y infection hinders potato defence response and renders plants more vulnerable to Colorado potato beetle attack - Marko Petek; Ana Rotter; Polona Kogovšek; Špela Baebler; Axel Mithöfer; Kristina Gruden (Molecular Ecology, 2014)
In the field, plants are challenged by more than one biotic stressor at the same time. In this study, the molecular interactions between potato ( S olanum tuberosum L.), Colorado potato beetle ( L eptinotarsa decemlineata Say; CPB ) and Potato virus Y NTN ( PVY NTN ) were investigated through analyses of gene expression in the potato leaves and the gut of the CPB larvae, and of the release of potato volatile compounds. CPB larval growth was enhanced when reared on secondary PVY NTN ‐infected plants, which was linked to decreased accumulation of transcripts associated with the antinutritional properties of potato. In PVY NTN ‐infected plants, ethylene signalling pathway induction and induction of auxin response transcription factors were attenuated, while no differences were observed in jasmonic acid ( JA ) signalling pathway. Similarly to rearing on virus‐infected plants, CPB larvae gained more weight when reared on plants silenced in JA receptor gene ( coi1 ). Although herbivore‐induced defence mechanism is regulated predominantly by JA , response in coi1 ‐silenced plants only partially corresponded to the one observed in PVY NTN ‐infected plants, confirming the role of other plant hormones in modulating this response. The release of β‐barbatene and benzyl alcohol was different in healthy and PVY NTN ‐infected plants before CPB larvae infestation, implicating the importance of PVY NTN infection in plant communication with its environment. This was reflected in gene expression profiles of neighbouring plants showing different degree of defence response. This study thus contributes to our understanding of plant responses in agro‐ecosystems.